2010
DOI: 10.1104/pp.110.165027
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cytosolic Phosphoglucomutase Compromises Gametophyte Development in Arabidopsis

Abstract: Cytosolic phosphoglucomutase (cPGM) interconverts glucose-6-phosphate and glucose-1-phosphate and is a key enzyme of central metabolism. In this study, we show that Arabidopsis (Arabidopsis thaliana) has two cPGM genes (PGM2 and PGM3) encoding proteins with high sequence similarity and redundant functions. Whereas pgm2 and pgm3 single mutants were undistinguishable from the wild type, loss of both PGM2 and PGM3 severely impaired male and female gametophyte function. Double mutant pollen completed development b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 55 publications
3
49
0
Order By: Relevance
“…Samples of the neutralized soluble fraction (200 mL) were applied to sequential 1.5-mL columns of cation exchanger Dowex 50 W and anion exchanger Dowex 1 (Sigma-Aldrich). Neutral compounds were eluted with 5 mL of water, lyophilized, redissolved in 200 mL of water, and separated on a CarboPac PA20 column on an ICS-3000 system (Dionex) as previously described (Egli et al, 2010). Peaks were identified by coelution with known malto-oligosaccharide standards and areas were determined using the instrument's Chromeleon software.…”
Section: Quantification Of Starch and Leaf Soluble Sugarsmentioning
confidence: 99%
“…Samples of the neutralized soluble fraction (200 mL) were applied to sequential 1.5-mL columns of cation exchanger Dowex 50 W and anion exchanger Dowex 1 (Sigma-Aldrich). Neutral compounds were eluted with 5 mL of water, lyophilized, redissolved in 200 mL of water, and separated on a CarboPac PA20 column on an ICS-3000 system (Dionex) as previously described (Egli et al, 2010). Peaks were identified by coelution with known malto-oligosaccharide standards and areas were determined using the instrument's Chromeleon software.…”
Section: Quantification Of Starch and Leaf Soluble Sugarsmentioning
confidence: 99%
“…Impairment or loss of function of enzymes contributing to the cytosolic hexose phosphate pool has recently been investigated for the Glc1P-forming enzyme PGM (Egli et al, 2010). The Arabidopsis genome encodes three PGM isoforms, with PGM1 localized to plastids and PGM2 and PGM3 localized to the cytosol (Caspar et al, 1985;Egli et al, 2010).…”
mentioning
confidence: 99%
“…The Arabidopsis genome encodes three PGM isoforms, with PGM1 localized to plastids and PGM2 and PGM3 localized to the cytosol (Caspar et al, 1985;Egli et al, 2010). Analyses of transfer DNA (T-DNA) mutants showed that homozygous pgm2/pgm3 double mutants were nonviable because of impaired gametophyte development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral sugars were eluted from sequential ion exchange columns of Dowex 50W and Dowex 1 (Sigma-Aldrich) and analyzed by high-performance anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD) as described by Egli et al (2010). Standard solutions containing known amounts of maltose (5 mM to 0.8 mM) and MOS DPs of three to seven (25 nM to 0.8 mM) were used to identify and quantify MOSs.…”
Section: Starch and Water-soluble Polysaccharide Extraction And Quantmentioning
confidence: 99%